2020
DOI: 10.1097/prs.0000000000006813
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Analysis of Rhytidectomy Using the Tracking Operations and Outcomes for Plastic Surgeons Database with 13,346 Patients

Abstract: Background: Rhytidectomy is a popular procedure for facial rejuvenation, but an up-to-date, comprehensive, and broadly representative appraisal is lacking. Methods: A cohort of patients undergoing rhytidectomy between 2008 and 2016 was identified from the Tracking Outcomes in Plastic Surgery database. Perioperative data and patient characteristics were analyzed with respect to adverse events. Multivariate logistic regression was used to identify associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Although the response rate (11 percent) was less than ideal, it is similar to that of previous ASPS face lift surveys. 1,4 Furthermore, a nonresponder analysis found that more than 20 percent of surveyed surgeons who practice predominantly aesthetic surgery responded, and general demographics of ASPS members, nonresponders, and responders are comparable ( see Document, Supplemental Digital Content 2 , which shows the nonresponder analysis, http://links.lww.com/PRS/F52).…”
Section: Discussionmentioning
confidence: 99%
“…Although the response rate (11 percent) was less than ideal, it is similar to that of previous ASPS face lift surveys. 1,4 Furthermore, a nonresponder analysis found that more than 20 percent of surveyed surgeons who practice predominantly aesthetic surgery responded, and general demographics of ASPS members, nonresponders, and responders are comparable ( see Document, Supplemental Digital Content 2 , which shows the nonresponder analysis, http://links.lww.com/PRS/F52).…”
Section: Discussionmentioning
confidence: 99%
“…Extended operative durations are also associated with greater complications. 24,25 Nevertheless, with greater experience, it is anticipated that operative duration will improve. Other drawbacks may include patient positioning in prone or decubitus, and staged procedures for bilateral reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“… 49 A 2020 review of the TOPS database identified a 0.89% incidence of infection following facelift surgery. 8 This study, however, did not identify the depth of infection, causative organism, or treatment. While the reported incidence is low, large retrospective reviews and surveys almost certainly underestimate the true incidence of infection, particularly minor cases of cellulitis.…”
Section: Common Complicationsmentioning
confidence: 93%
“… 9 A 2020 database review of 13,346 facelifts identified 2 patients who developed pulmonary emboli (incidence 0.01%). 8 This study did not provide information regarding DVT prophylaxis or anesthetic modality.…”
Section: Common Complicationsmentioning
confidence: 98%
See 1 more Smart Citation